Baseline serum sitosterol level as predictor of adverse clinical events in acute coronary syndrome patients with dyslipidaemia: A sub-analysis of HIJ-PROPER. (July 2018) - Yamaguchi, Junichi; Kawada-Watanabe, Erisa; Koyanagi, Ryo; Arashi, Hiroyuki; Sekiguchi, Haruki; Nakao, Koichi; Tobaru, Tetsuya; Tanaka, Hiroyuki; Oka, Toshiaki; Endo, Yasuhiro; Saito, Katsumi; Uchida, Tatsuro; et al.
Abstract: Background and aims: We aimed to examine the effect of serum sitosterol, a cholesterol absorption marker, on clinical outcomes in acute coronary syndrome patients with dyslipidaemia. Methods: This is a sub-analysis of the HIJ-PROPER trial that assesses the effect of aggressive low-density lipoprotein cholesterol (LDL-C) lowering treatment with pitavastatin + ezetimibe in 1734 acute coronary syndrome (ACS) patients with dyslipidaemia. Patients were divided into two groups based on sitosterol level at enrolment (cut-off value was 2.2 μg/mL; a median of baseline sitosterol level), and clinical outcomes were examined. Results: The mean LDL-C level after 3 years in the low sitosterol group was 84.8 ± 20.1 mg/dL with pitavastatin-monotherapy and 64.6 ± 20.3 mg/dL with pitavastatin + ezetimibe, while corresponding values in the high sitosterol group were 91.0 ± 22.9 mg/dL and 71.1 ± 23.3 mg/dL, respectively. In the high sitosterol group, the Kaplan-Meier event rate for the primary endpoint at 3 years was 26.0% in the pitavastatin + ezetimibe group, as compared with 34.3% in the pitavastatin-monotherapy group (hazard ratio, 0.71; 95% confidence interval, 0.56–0.91; p  = 0.006, p -value for interaction = 0.010). However, in the low sitosterol group, there was no significant reduction of the primary endpoint by pitavastatin + ezetimibe therapy. Conclusions: Aggressive lipid-lowering treatment with ezetimibe had a positive effect on clinical outcomes in the high sitosterol subset of ACS patients with dyslipidaemia, but not in the low sitosterol subset. This effect was independent of LDL-C reduction and suggests that sitosterol measurement on admission in ACS patients might contribute to a "personalised" lipid-lowering approach. Highlights: Serum sitosterol affects clinical outcomes in acute coronary syndrome patients. Pitavastatin + ezetimibe reduce adverse outcomes only in high-sitosterol patients. This effect is independent of low-density lipid cholesterol reduction.